Inovation Of Collagen Based Corneal Hydrogel with the Addition Of Glycopolymer As the Solution For Irreversible Blindness By Corneal Ulcers - sandyakala, disca (Journal of Stem Cell Research and Tissue Engineering, 2019)
Indonesian Health MinistryÂ  Data showed that 5.3% of 100,000 population in Indonesia suffer from corneal ulcers. Corneal ulcer is one of the five leading causes of largest blindnessÂ  morbidity and loss of vision. Corneal transplant being the only medicine accepted widely despite there are many post-surgery complications. The study was conducted to review the initials make a synthetic cornea from natural ingredients collagen type I composite with a glikopolimer from poly (1,8-octanediol-co-citrate) (POC) and poly (vynyl-alcohol) (PVA) hydrogels form to review increase the strength of mechanical and biodegradibilty as candidate synthetic cornea. The result of Fourier Transform Infra Red (FTIR) tin that strong cross Occurs on Force C = O stretching Which is a cluster formation of ester IN 1735 cm-1. The result of tensile test showed that the value of elasticity modulus tends to decrease with increasing concentration of collagen with modulus of elasticity in a row for a review variation collagen 1%, 3%, and 5% is 13.26 MPa, 13.21 MPa, and 11.5 MPa. Moisture balance test results Phosphate Buffer Saline (PBS) for 7 days for a review sample of collagen Variation 1%, 3%, and 5% is 89%, 91% and 92%. Spectroscopic test results showed that all the various samples can continue light until appoximately 98% accordance to standart of cornea. The synthetic cornea from collagen type 1 and glycopolymer from poly(1,8-octanediol-co-citrate) (POC) and poly(vynyl alcohol) (PVA) have a potential to be solution for irreversible blindness caused by corneal ulcers.